2016
DOI: 10.1590/2446-4740.01316
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the use of a robot to improve social skills in children with autism spectrum disorder

Abstract: Introduction: Autism Spectrum Disorder is a set of developmental disorders that imply in poor social skills, lack of interest in activities and interaction with people. Treatments rely on teaching social skills and in such therapies robotics may offer aid. This work is a pilot study, which aims to show the development and usage of a ludic mobile robot for stimulating social skills in ASD children. Methods: A mobile robot with a special costume and a monitor to display multimedia contents was designed to intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…Note, extant information on social mediator hypothesis mostly comes from pilot studies or technical reports, without control condition, descriptive and inferential statistics (Werry et al, 2001;Robins et al, 2009;Iacono et al, 2011;Shamsuddin et al, 2012) and/or without diagnostic method, exclusion and inclusion criteria, developmental age etc. (Feil Seifer and Mataric, 2009;Valadao et al, 2016). Further studies could better comply with the requirements of clinical methodology.…”
Section: Social Mediatormentioning
confidence: 99%
“…Note, extant information on social mediator hypothesis mostly comes from pilot studies or technical reports, without control condition, descriptive and inferential statistics (Werry et al, 2001;Robins et al, 2009;Iacono et al, 2011;Shamsuddin et al, 2012) and/or without diagnostic method, exclusion and inclusion criteria, developmental age etc. (Feil Seifer and Mataric, 2009;Valadao et al, 2016). Further studies could better comply with the requirements of clinical methodology.…”
Section: Social Mediatormentioning
confidence: 99%
“…Also, most of the robots developed for use in autism therapy are smaller than the children hence makes interaction a bit difficult. Self-presentation modes are virtually nonexistent in most robots used in autism therapy [17]. Before the robot-child interaction, robot self-presentation (i.e robot introducing itself) would help the child familiarize with the robot and also create a form of emotional bond.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Werry et al [5], children with ASD were made to interact with a robot and a non-animated toy; findings suggested that the children had more physical contacts, interactions and eye gazes with the robot as compared to the toy. [17].…”
Section: Robotic Systems For Autistic Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…A new version of the robot, called N-MARIA (New-MARIA), with a better design, is shown in Figure 1. For more information about the robot see Valadão et al (2016).…”
Section: Introductionmentioning
confidence: 99%